2019
DOI: 10.1007/s00421-019-04128-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiological comparison between non-athletes, endurance, power and team athletes

Abstract: We hypothesized that endurance athletes have lower muscle power than power athletes due to a 25 combination of weaker and slower muscles, while their higher endurance is attributable to better oxygen 26 extraction, reflecting a higher muscle oxidative capacity and larger stroke volume. 27 Endurance (n=87; distance runners, road cyclists, paddlers, skiers), power (n=77; sprinters, throwers, 28 combat sport athletes, body builders), team (n=64; basketball, soccer, volleyball) and non-athletes 29 (n=223) performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 42 publications
1
49
0
1
Order By: Relevance
“…We have previously demonstrated that a concentric geometry is peculiar of adolescent athlete of African ethnicity, who also develop greater LV hypertrophy, similar to adult athletes . African adolescents, even if undergoing resistance training, develop a concentric than eccentric hypertrophy rather like in power sports . These data explain the greater incidence of ERp in adolescent athletes of African ethnicity.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We have previously demonstrated that a concentric geometry is peculiar of adolescent athlete of African ethnicity, who also develop greater LV hypertrophy, similar to adult athletes . African adolescents, even if undergoing resistance training, develop a concentric than eccentric hypertrophy rather like in power sports . These data explain the greater incidence of ERp in adolescent athletes of African ethnicity.…”
Section: Discussionmentioning
confidence: 66%
“…Second, the absence of female black athletes in this study is certainly a limitation for elucidating comparison with Caucasian ones. Third, our healthy population is selected for echocardiography analysis during the cardiovascular screening for sport eligibility and, therefore, there cannot be a control group . Non‐professional athletes played different disciplines that induce different LV remodeling .…”
Section: Limitationsmentioning
confidence: 99%
“…The stroke volume was 70-77 ml for male athletes who compete, which was significantly higher than the 50-60 ml stroke volume of an untrained male mentioned in the literature (Utomi et al, 2013). During the testing, the stroke volume of amateur athletes was lower than in professional athletes (160-180 ml), and higher than in untrained persons (100 ml) (Degens et al, 2019). The study showed that during the exercise, the stroke volume depended on duration of the training programme.…”
Section: Discussionmentioning
confidence: 61%
“…It is influenced by maximal cardiac output and the arterio-venous oxygen difference [16]. Power athletes have lower values than team and endurance athletes [16,17]. However, this difference could be attributed to a higher cardiac output as a consequence of a higher cardiac adaptation [18] as well as to a larger oxygen carrying capacity and/or oxygen extraction by endurance athletes [17].…”
Section: Introductionmentioning
confidence: 99%
“…Power athletes have lower values than team and endurance athletes [16,17]. However, this difference could be attributed to a higher cardiac output as a consequence of a higher cardiac adaptation [18] as well as to a larger oxygen carrying capacity and/or oxygen extraction by endurance athletes [17]. Still, evaluating the during a standard cardiopulmonary exercise test should allow a classification of climbing when performed by elite climbers, especially when compared to elite Nordic skiers, a sport classified as an endurance sport, when performing the same non-sport-specific test, namely a cycle test.…”
Section: Introductionmentioning
confidence: 99%